Influence of technical and technological parameters on the barley dehulling process - Kharchenko, Yevgen; Buculei, Amelia; Chornyi, Valentyn; Sharan, Andrii (My University, 2022)
The research aim is to determine effect of duration of dehulling, the barley size and moisture, the rotation speed of abrasive discs, the abrasive grit and the load factor of the dehuller on the dehulling index. The dehulling was carried out in laboratory dehuller (model ULZ-1) at the rotation speed of abrasive discs of 29.6±0.015 s-1 (1775±0.9 rpm) and 42.3±0.013 s-1 (2540±0.8 rpm) and removing of barley husks and meal was conducted in the laboratory aspiration duct of 60 mm width. The research has shown that the increase in the dehulling duration the weight of the barley loaded to the dehuller, the rotating rate of abrasive discs and the load coefficient of the dehuller working chamber leads to the dehulling index rise. There exists the non linear dependence between the load coefficient of the dehuller working chamber with the minimum point of the dehulling index for the large fraction of barley 0.27–0.28 and for the small fraction of barley 0.24–0.25. The influence of the barley weight and the load coefficient of the working chamber of the dehuller on the dehulling index occurs according to the curvilinear dependence with the minimum point of the dehulling index for the large barley fraction of 0.27–0.28 and for the small barley fraction of 0.24–0.25. The increase in the processing duration and the load coefficient of the working chamber of the dehuller leads to the increase of the dehulling index, but at the same time the minimum point of the dehulling index decreases from 0.29 to 0.25. As the size of the barley grows, the dehulling index decreases. The gain in moisture of the barley leads to the decrease of the dehulling index according to the linear dependence for both large and small barley fractions. Moreover, the small fraction has the bigger values of the dehulling index than the large one. The moisture influence on the dehulling index has linear dependence for both large and small barley fractions. As moisture increases the dehulling index decreases linearly, but at the same time the large barley fraction had lower values of the dehulling index than the small one. The increase in abrasive discs grit leads to the dehulling index decrease according to the curvilinear dependence. At the grit of 80 the dehulling index gets the constant value and its change depends on the duration of processing. The influence of technological parameters of barley grain on the dehulling index has linear dependence, and machine parameters affect the dehulling index according to curvilinear dependency. These results must be considered when evaluating the effectiveness of dehulling and the development of the process model. Мета – дослідити залежність індексу лущення від тривалості обробки, вологості та крупності зерна ячменю, частоти обертання абразивних дисків, зернистості та маси зерна, завантаженого в лущильник, а також коефіцієнта завантаження робочої камери машини. Лущення зерна здійснювалося в лущильнику УЛЗ-1 при швидкості обертання абразивних дисків 29,6±0,015 с-1 (1775±0,9 об/хв) та 42,3±0,013 с-1 (2540±0,8 об/хв). Виділення лузги та мучки із зерна ядра ячменю здійснювали в лабораторному аспіраційному каналі із шириною 60 мм. Дослідження показали, що збільшення тривалості лущення, маси зерна ячменю, яка завантажена в лущильник, частоти обертання абразивних дисків і коефіцієнта завантаження робочої камери лущильника призводить до збільшення індексу лущення. Існує нелінійна залежність між коефіцієнтом завантаження робочої камери лущильника з точкою мінімуму індексу лущення для крупної фракції 0,27–0,28, для дрібної фракції ячменю – 0,24–0,25. Вплив маси ячменю і коефіцієнта завантаження робочої камери лущильника на індекс лущення відбувається за криволінійною залежністю з точкою мінімуму для крупної фракції ячменю 0,27–0,28, для дрібної – 0,24–0,25. Збільшення тривалості обробки і коефіцієнта завантаження робочої камери лущильника призводить до збільшення індексу лущення, але при цьому точка мінімуму індексу лущення зменшується з 0,29 до 0,25. При збільшенні розміру зерна ячменю індекс лущення знижується. Збільшення вологості ячменю призводить до зниження індексу лущення за лінійною залежністю як для крупної, так і дрібної фракції ячменю. При цьому дрібна фракція має більші значення індексу лущення, ніж крупна. Вплив вологості зерна на індекс лущення ячменю має лінійну залежність як для крупної, так і для дрібної фракції. Зі збільшенням вологості індекс лущення лінійно зменшується, але при цьому крупна фракція ячменю має більш низькі значення індексу лущення, ніж дрібна. Збільшення зернистості абразивних дисків призводить до зниження індексу лущення за криволінійною залежністю. При зернистості 80 індекс лущення приймає постійне значення і його зміна залежить від тривалості обробки зерна. Дослідженнями встановлено, що вплив технологічних параметрів зерна ячменю на індекс лущення має лінійні залежності, а параметри машини впливають на індекс лущення за криволінійними залежностями. Результати цього дослідженнями необхідно враховувати при оцінюванні ефективності лущення та подальшому розробленні моделі процесу.
Keywords: peeling index; лущення зерна; grain husking; кафедра технології зберігання і переробки зерна; кафедра технології зберігання і переробки зерна; кафедра технології зберігання і переробки зерна; кафедра технології зберігання і переробки зерна